Profitability Through Analysis of Amount of Credit and Liquidity Levels - Ari Bramasto; Sri Dewi Anggadini (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
Bank's business activities cannot be separated from public trust, so the health level of the bank needs to be maintained and the application of prudential principles in running its business. Banks are required to maintain the soundness level of the bank by paying attention to asset quality, capital adequacy, liquidity, management quality, and profitability, as well as solvency. This research has formulated several problems, namely: the relationship between the amount of credit, the level of liquidity, and profitability and to find out how much influence the amount of credit, the level of liquidity to profitability through Return on Assets (ROA). The purpose of the authors in conducting research is: to determine the relationship between the amount of credit, the level of liquidity, and profitability and to determine the influence of the amount of credit, the level of liquidity on profitability using ROA. The results of this study are recommended as input and information about the application of the amount of credit and the level of liquidity that can be used as the basis for the profitability as measured by ROA.